Roles & Responsibilities of Notaries Regarding the Deed of Will which is Made In front of Notary - Nurani, M. Syaefudin; Hasana, Dahniarti (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This legal research aims to know the role of a notary in the settlement of a will made before a notary, the responsibility of a notary to a will made before a notary and how is an example of a testament deed made by a notary. This research is a sociological juridical research Â with descriptive research specifications. Data sources and data collection methods used primary and secondary data which were analyzed qualitatively. The results of this study indicate that Obligations that must be carried out by a notary after a will is made are obliged to notify all testament acts that he made to the Central List of Wills (DPW) and Heritage Hall (BHP) both open testament (Openbaar Testament), written testament (olographis testament), or closed or confidential testament. Thus the notary has a very important role and the notary's responsibility for the testament act made before him, namely moral responsibility, ethical responsibility, and legal responsibility consisting of formal and material aspects. With respect to a testament act made before him, the notary is responsible for reading it out in front of witnesses. After that, the notary will notify the testament act to the Central List of Wills, the Directorate of Civil Affairs, the Directorate General of General Legal Administration, the Ministry of Law and Human Rights and the Relic Treasure Hall (BHP).